Pemahaman Warga Matematika terhadap Konteks Visi, Misi, Tujuan Program Studi Pendidikan Matematika - Mazlan Mazlan (At-Tarbawi : Jurnal Pendidikan, Sosial dan Kebudayaan, 2019)
The purpose of this study is to explain the level of student understanding of the context of the vision, mission, and objectives of the Mathematics Education Study Program (PMA Study Program). This study uses a quantitative descriptive approach. The questionnaire used is an open and closed questionnaire, meaning the questionnaire contains questions with four (4) answer choices and is accompanied by an explanation of the choice of the answer. The research sample was set at 20%, namely as many as 61 students from each semester. The results of the study show; (1) almost all students are 60 people (98.36%) who understand the context of the vision of superior words, 13 people including very understanding (21.31%) and able to interpret professional words, and 60 people are very understanding (98.36% ) and able to interpret the words Rahmatan Lil Alamin, (2) Students almost entirely understand the mission of the first PMA Study Program (98.36%), and so on with the same percentage for the second, third, and fourth missions, (3) Level Mathematicians' understanding of the context of the Study Program's objectives is to understand only the first goal with the number of students 55 students (90.16%), while the second, third, fourth, fifth and sixth goals are in the very understand category of 9 people (14.75%). So, in general, it can be said that PMA Study Program students almost all understand the context of the new PMA vision, mission, and objectives of the Study Program